An Analysis of Activity, Intensity and Structural Effect on Change in Energy Consumption in Bangladesh using Complete Decomposition Model (CDM) - Khosruzzaman, S; Asgar, MA; Asgar, MA; Rahman, KMR; Akbar, S (Bangladesh Journal of Scientific and Industrial Research, 2012)
For the purpose of identifying the vulnerable aspects of our energy problem and to seek an appropriate solution, the total energy supply, energy demand and energy consumption need to be analyzed in respect of their components. We have used the decomposition model for analyzing the correlation between energy consumption and economic development up to 2007 taking 1990 as the base year. The relative impacts of activity, intensity and structure effect are analyzed for different economic sectors in Bangladesh. Moreover, the country's economy is disaggregated in to two groups' namely low energy intensive group and high-energy intensive group. The trends of energy uses in the above groups are also evaluated to provide a basis for assessment of sustainability. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10726 Bangladesh J. Sci. Ind. Res. 47(1), 61-68, 2012